Analyzing the features of material nonlinearity evaluation in a rectangular aluminum beam using Rayleigh waves: theoretical and experimental study - Masurkar, Faeez (2019)
This study proposes a new parameter to evaluate the material nonlinearity in a thick Aluminum (Al) beam having rectangular cross section using Rayleigh waves. This parameter yields a true value of material nonlinearity using the amplitudes of Rayleigh wave harmonics, in contrast to the relative value yielded by the conventional nonlinearity parameter β′. The Rayleigh wave harmonics are generated in a thick Al 1100 specimen through experiments to estimate its inherent material nonlinearity. This inherent nonlinearity is embedded in the material via lattice elasticity and reckoned using the higher order elastic coefficients. With this experimental investigation, it is found that the accurate evaluation of material nonlinearity is highly dependent on the tone burst cycles in the excitation signal. It is also found that there is a small amount of contribution to the material nonlinearity parameter from the imaginary part of the shear wave component. Furthermore, the relationship between material nonlinearity evaluated using the proposed parameter, excitation frequency, propagation distance, and tone burst cycles in the excitation signal have been unveiled. After knowing these relationships, the material nonlinearity evaluated using the proposed parameter is compared with that obtained from a physics-based nonlinearity parameter containing higher order elastic coefficients. The deviation between the results is minimal. Thus, with the use of amplitudes of harmonics of the Rayleigh wave generated through the experiments, the proposed parameter can evaluate the true material nonlinearity of thick Al beams with fair accuracy.